2014
DOI: 10.1021/nn504431e
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Redistribution in Molecular Nanostructures Mediated by Metal–Organic Bonds

Abstract: Dicyanovinyl-quinquethiophene (DCV5T-Me2) is a prototype conjugated oligomer for highly efficient organic solar cells. This class of oligothiophenes are built up by an electron-rich donor (D) backbone and terminal electron-deficient acceptor (A) moieties. Here, we investigated its structural and electronic properties when it is adsorbed on a Au(111) surface using low temperature scanning tunneling microscopy/spectroscopy (STM/STS) and atomic force microscopy (AFM). We find that DCV5T-Me2 self-assembles in exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
41
1
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 55 publications
(124 reference statements)
0
41
1
5
Order By: Relevance
“…Adjacent cyano groups point toward thiophene units of neighboring molecules. In contrast to similar molecular chains found for the stiffer DCV5T species on Au(111), here we observe no coordinative Au adatoms mediating the intermolecular bonding. DCV6T chains are pure organic architectures stabilized by bare intermolecular interactions.…”
contrasting
confidence: 95%
See 1 more Smart Citation
“…Adjacent cyano groups point toward thiophene units of neighboring molecules. In contrast to similar molecular chains found for the stiffer DCV5T species on Au(111), here we observe no coordinative Au adatoms mediating the intermolecular bonding. DCV6T chains are pure organic architectures stabilized by bare intermolecular interactions.…”
contrasting
confidence: 95%
“…This technique has been widely utilized to identify and characterize the structural and electronic details of individual molecules, including their conformation, adsorption geometry, bond order, and charge distribution . Although noncovalent bonds cannot be directly resolved in AFM images, several studies have demonstrated that the bonding structure can be precisely determined from the atomically resolved molecular arrangement . However, a detailed study of changes in geometric structure when the molecule's environment is altered by intermolecular interactions has not been addressed with AFM experimentally until now.…”
mentioning
confidence: 99%
“…11 Furthermore, a few examples of surface metal-coordination bond involving Au atoms were recently demonstrated. 7,12 Here, we present the controlled fabrication of discrete coordination nanostructures formed by two or three molecules on a gold surface. For this goal, we specifically designed the cyanosexiphenyl molecule, schematically shown in Figure 1a, which is an evaporable, nonsymmetrical, π-conjugated molecule.…”
mentioning
confidence: 99%
“…[49] Unterschiede in der molekularen Adsorptionshçhe kçnnen mit einer Genauigkeit von 3pmg emessen werden und Neigungen der Molekülebene zur Substratebene werden mit einer Genauigkeit von 0.18 8 erfasst. [73][74][75] Die Adsorptionsgeometrie von Pentacen auf Cu(111) ist in Abbildung 2als Karte der Messspitzenhçhe z*dargestellt, welche aus einer 3D-Kraftkarte extrahiert wurde. [69] Molekulare Konformationen kçnnen präzise voneinander unterschieden und aufgelçst werden.…”
Section: Adsorptionsgeometrieunclassified
“…[49] Die Hçhe z*i st die Hçhe der Spitze z,b ei der die Frequenzverschiebung minimal ist. [40,74] Insbesondere bei wenig stabilen Systemen bietet AFM eine gute Mçglichkeit zur Bildgebung,z .B.b ei der Strukturbestimmung von Wasserclustern auf Oberflächen. Die Spitzenhçhe z*ist im Df(z)-Spektrum ein jeweils charakteristischer Punkt.…”
Section: Adsorptionsgeometrieunclassified